ECI-SCBC: An Efficient Collaborative Interaction method for Supply Chain Based on Blockchain Consensus Mechanism - Wang, Jinli; Zhao, Hang; Liu, Mengzhuang; Yuan, Zehui; Feng, Libo; Yu, Yimin; Li, Hui; Yao, Shaowen (Computers & industrial engineering, 2025)
In the field of intelligent manufacturing supply chains, there are issues such as difficult node collaboration, non- transparent information transmission, and high management costs. To address these challenges, this paper proposes an Efficient Collaborative Interaction Mechanism for Supply Chain Based on Blockchain Consensus Algorithm (ECI-SCBC). First, based on the Delegated Proof of Stake (DPoS) consensus algorithm, a vote weight constraint model is established by introducing counting weight constraints, enabling multiple nodes to participate collaboratively in voting events. Second, a DPoS-based incentive model is developed, introducing a dual-reward mechanism that motivates nodes through rewards for both supply chain and blockchain-related contributions. Third, the reputation model, voting mechanism, and incentive mechanism are integrated and applied in DPoS, forming RVI- DPoS. This mechanism enables efficient collaboration among nodes and trustworthy transmission of information. Experimental results show that the node participation rate reaches 87%, the error rate is reduced to 9%, and the transaction processing capacity (TPS) achieves 2,637 units per second. These findings indicate that employing advanced blockchain- based collaborative interaction methods and optimizing resource utilization can significantly enhance system performance, efficiency, and security. Furthermore, the proposed model demonstrates the potential to achieve efficient collaboration and information transparency in complex and dynamic real world supply chain environments. •A collaborative mechanism is proposed for supplychain’s stability and efficiency.•We hardened DPoS with a voting-weight cap to curb rogue nodes.•RVI-DPoS fuses reputation, vote and reward for trusted, agile supply-chain data flow.